Development and fieldwork trial of autonomous surface vehicles for bathymetry mapping - Naing, Lwinthein; Mohd Ghani, Ahmad Shahril; Sahalan, Muhammad Irsyad; Abdul Aziz, Mazlan; Zainal Abidin, Zulkifli; Rashid, Muhammad Mahbubur (Institute of Electrical and Electronics Engineers Inc., 2018)
The paper is about development and fieldwork trial of Autonomous Surface Vehicles (ASVs) for bathymetry. Due to the increasing demand on water monitoring and ocean exploration, ASVs are being developed to assist humans to reduce the time and resources required while increasing the efficiency of the tasks. Each developed ASV is equipped with Global Positioning System (GPS) and multi-sensor that can measure depth, speed, and temperature of the water. The ASVs can be either manually controlled through remote controls (RCs) or automatically controlled through mobile phone that has waypoint navigation software. The data collected by individual ASV are wirelessly transmitted to and can be viewed in real-time at the ground station. The data collected then can be analyzed and used for depth and temperature simulation of the water at specific locations. The ASVs were deployed at several lakes and seas to evaluate their performance in terms of data collection and navigation under different environmental conditions.